2007
DOI: 10.4314/as.v4i2.1531
|View full text |Cite
|
Sign up to set email alerts
|

Effects of N-fertilization and spacing on african rice gall midge <i> Orseolia oryzivora </i> harris and gagn&eacute i a sub-humid area of southeastern Nigeria

Abstract: Nitrogen fertilization and spacing hold a strong promise in the integrated management of rice insect pest problem. Therefore, three levels of urea: 0, 80 and 160 kg N ha-1 and three spacings: 10-cm x 10-cm, 20-cm x 20-cm and 30-cm x 30-cm were evaluated for two years in Abakaliki, Nigeria, for the control of rice gall midge. The experiment was set up using split-plot arrangement in a randomized complete block design (RCBD) with three replications. Results of the trial showed that nitrogen significantly increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…The effect of fertilizer inputs has also described by Sarwar (2011) who reported how important is the plant nutrient in changing population dynamics of herbivores apart from being a good indicator in improving host plant quality. This was further supported by the study by Ogah et al (2005) who reported increased rice gall midge damages in Nitrogen applied plots as compared to the control.…”
Section: Journal Of Agricultural Sciencesupporting
confidence: 70%
“…The effect of fertilizer inputs has also described by Sarwar (2011) who reported how important is the plant nutrient in changing population dynamics of herbivores apart from being a good indicator in improving host plant quality. This was further supported by the study by Ogah et al (2005) who reported increased rice gall midge damages in Nitrogen applied plots as compared to the control.…”
Section: Journal Of Agricultural Sciencesupporting
confidence: 70%
“…Ogah et al (2005) have suggested that delayed sowing may reduce the incidence of O. oryzivora in southeastern Nigeria, by reducing the period during which rice plants are available for infestation by the midge. This suggests that alteration of the planting period according to climatic factors could affect the incidence of O. oryzivora.…”
Section: Discussionmentioning
confidence: 99%
“…The African rice gall midge (AfRGM) Orseolia oryzivora Harris and Gagné (Diptera: Cecidomyiidae) is the most serious insect pest of lowland and irrigated rice (Williams et al, 1999;Ogah et al, 2005Ogah et al, , 2009Nwilene et al, 2006). Indigenous to Africa, the insect's status has changed during the last two decades from a minor to a major pest, and in several countries in Africa, it causes perennial economic damage to rice (Nacro et al, 1996;Singh et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This enrichment could further reduce pesticide intake due to the negligible presence of pests, reduce yield losses and increase farmers' incomes for the sustainable development of rice. On the other hand, the incidence of midge increases with increasing levels of nitrogen fertilization [24]. The latter also showed that stem borers' attack was positively correlated with soil moisture and nitrogen content, hence the strong presence of white panicles and Yaoundé, compared to Ntui.…”
Section: Physico-chemical Parametersmentioning
confidence: 85%